Enhancing the safety and reliability for loading and unloading bulk storage bags and a new bulk feeder support design structure. (28th October 2022) - Alkhaledi, Khaled; Means, Kenneth; Dalalah, Doraid
Super bags are used to pack large and heavy bulk materials. They are durable; however they can be damaged by improper handling or misuse. Ensuring the safety of the operators who handle heavy bags is a main concern. The first objective is designing a backup safety frame to support the suspended bags by the hoist. The second objective is designing a spider bag support system compatible with the new frame and able to lift the super bag as required by Occupational Safety and Health Administration 1926.554 standard. Minimising weight and reducing cost were taken into consideration. The new frame and spider combined design mechanical properties were simulated using ANSYS™ software. The results showed the maximum deflection found at the spider was 1.78 × 10 -3 m, while the maximum strain was 0.0006 for 250 MPa material yield stress. The maximum stress was 100 Mpa located at the hopper's base. The combined design safety factor was 2.503 and fatigue safety factor was 1.45. This study concluded the new frame and spider structure will achieve the desired objectives and meet the OSHA regulations.